Pedagogical heritage of ethnic values in the process of self-education - Kenesbekova, S.; Ishanov, P.; Mukhametzhanova, A.O.; Kussainova, M.; Abitayeva, T. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
Modern ethno-pedagogical education is aimed at solving a number of problems: the entry of a future teacher, a university graduate into society, his productive adaptation and successful self-realization in a multicultural space; promoting the development of his professionalism and self-trait; ensuring the continuity of generations in the transmission of ethnic value system. This, in turn, requires the content filling of future teacher`s professional training by the formation of the professional and pedagogical self-educational competence of future teachers with special knowledge, that contributes to the professional and ethical development of his personality, the formation of ethno-pedagogical competence, his readiness for activities based on ethical norms of relationships in a particular ethno and a multicultural environment. Today, in public consciousness and activity, the human factor is justified as the determining factor in solving modern problems, and therefore the idea of a person's intrinsic value, the need to respect his personal dignity, spiritual experience, ethnicity, ethno-social role, rights to uniqueness, and to choose the path of cognition and life is discussed.
Өздік білім алу үдерісіндегі этникалық құндылықтардың педагогикалық мұрасы
Педагогическое наследие этнических ценностей в процессе самообразования
Keywords: professional pedagogical self-education; ethno-pedagogical competence; ethnic competence; pedagogical competency; “qualifications”; self-education; ethnic values; the worldview of an ethnic group; life activity and inherent value